The Importance of Friendship; Storytelling in Korean Music Industry by SEVENTEEN - Heidy Isabel; Setiawan, Joe Harrianto; Marwati, Annisa Rais (LSPR Institute of Communication & Business, 2024)
Hallyu or K-Pop or pop culture from South Korea divided into several generations, the third generation that truly blasted through their most distinguishable of developing and storytelling concepts, conveying more than music, but stories and own concepts. SEVENTEEN's storytelling conveyed messages about friendship lead to being a support system in the community seek answering the where some researchers also mentioned having a strong support system led to many positive benefits and with many estimations of adult over the world experienced loneliness to mental illness. Using the narrative paradigm and observing SEVENTEEN’s concerts and its contents to discover the meaning of SEVENTEEN’s storytelling. Based on Friendship research by Parker & Asher, founded SEVENTEEN growth, relationships, and life are all embodied in performances the members create together becoming the value they brought to the world. Their shared moments, music and performances lead to a positive special and unique relationship with their audience and establishing a supportive and affective environment throughout the community. SEVENTEEN lights up the positive energy, as a support system were it being able to minimize the negative effects from youth-hood period.